Study of Environment Economics According to Depletion and Degradation Values of Utilization of Natural Resources in the Regional Economy - Balaka, Muh. Yani; Gamsir, Gamsir; Hasddin, Hasddin; Kasim, Safril (International Journal of Energy Economics and Policy, 2023)
Any resulting development uses natural resources. Every resource that is extracted as development input has a negative impact and can be quantified through depletion and degradation values. The research aims to analyze the value of depletion and degradation of natural resources as a result of regional economic growth which is prorated in gross regional regional income or GDP. The results of this research are important new information and discourse for the government to balance economic growth and a green economy with the sustainability of natural resources. The basis is economic growth without and/or minimizing environmental degradation. The result is that of the 17 sectors, there are 9 sectors that extract natural resources. Depletion and degradation values occur in the base and non-base sectors. The resulting total value of depletion and degradation exceeds the national average as reported by relevant studies.